PENGEMBANGAN MODUL PEMBELAJARAN MATEMATIKA SD BERBASIS SCIENTIFIC UNTUK MAHASISWA PRODI PGSD UNIVERSITAS PGRI SILAMPARI - Mandasari, Novianti; Rosalina, Elya (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2024)
This study aims to produce a scientific-based elementary school mathematics learning module for students of the PGSD study program at PGRI Silampari University that is valid, practical and has potential effects. The research method used is development research with a 4D development model, consisting of the stages of Define, Design, Development and Disseminate. The instruments used to answer the research objectives are the validation questionnaire, practicality questionnaire, and Test. The data in this study were analyzed using the Aiken V and N-Gain formulas. development of a scientific-based elementary school mathematics learning development module in semester V of the PGSD Study Program at PGRI Silampari University, so it was concluded that from the three validators, namely language experts, material experts and media experts, an overall value of 0.91 was obtained. For the practicality test stage of lecturers and students with an overall percentage of 93.18. While for the effectiveness test stage after being analyzed by the researcher, a percentage value of 0.52 was obtained, therefore the scientific-based elementary school mathematics learning development module is feasible to use.